Comparison of tibial rotation strength in patients' status after anterior cruciate ligament reconstruction with hamstring versus patellar tendon autografts - Torry, M. R.; Decker, M. J.; Jockel, J. R.; Viola, R.; Sterett, W. I.; Steadman, J. R. (Clinical Journal of Sport Medicine, 2004)
Objective: To determine if there are tibial rotational strength deficits in individuals treated with a semitendinosus/gracilis or bone-patella tendon-bone (BTB) autografts for ACL reconstruction. Design: Retrospective. Setting: Clinical practice and nonprofit research site. Patients: 102 subjects-34 treated with BTB autograft, 34 treated with a hamstring autograft, and 34 matched controls-were evaluated at an average of 53.1 +/- 36.0 months postoperatively. Main Outcome Measurements: Isokinetic examination at 60, 120, and 180[degrees]/s to assess internal (IT) and external tibial (ET) rotation peak torque of the operated knee and contralateral knee. Internal and external tibial rotation peak torque values were evaluated for differences between gender and surgery type (2 x 3 ANOVA). Results: Contrasts of IT torque across groups revealed that surgery type exhibited a significant main effect (P < 0.0001), but gender did not (P = 0.07), and there was no interaction of surgery and gender (P = 0.64). The hamstring group was weaker in IT rotation compared with the BTB and control groups (P < 0.05). No difference was noted in IT rotation torque between BTB and control groups at all test velocities. Contrasts of ET rotation torque across groups revealed that surgery type exhibited a significant main effect (P < 0.0001), but gender did not (P = 0.48). There was no interaction of surgery and gender (P = 0.98). The BTB group was significantly weaker compared with the hamstring group (P < 0.001) and the control group (P < 0.001) in ET at all test velocities. Conclusions: Residual strength deficits in IT and ET rotation following hamstring graft and BTB graft ACL reconstruction are apparent.